PENGARUH PELATIHAN TENAGA KERJA TERHADAP JUMLAH PRODUKSI KULIT PADA LINGKUNGAN INDUSTRI KECIL (LIK) KABUPATEN MAGETAN - Ika Nor Wahyuni (Universitas PGRI Madiun, 2016)
This study aims to determine the skin workforce training entrepreneurs in Environment Industri Kecil (LIK) Magetan, to determine the amount of production in the skin entrepreneurs Environment Industri Kecil (LIK) Magetan, and to find out how the influence of the number of workforce training leather production in the Environment Industri Kecil (LIK) Magetan. The samples in this study used a sample of employers in the region aimed at the Lingkungan Industri Kecil (LIK) who attended training in UPT Industri Kulit dan Produk Kulit Magetan who are 32 employers. Data collection using questionnaires and documentation. In analyzing the data in the study using the product moment correlation test, F test and t test. In analysis regression results in correlation values obtained for rcount0.668 > rtable of 0,349 or Sighit 0,000 < Sigprob 0.05 means training workers had skin relation to total production in the Lingkungan Industri Kecil (LIK) Magetan. While the Fisher test values obtained Fcount 24.135 > Ftable 4.17 or Sighit 0,000 < Sigprob 0.05 means workforce training have an influence on the amount of skin on the production of Environment Industri Kecil (LIK) Magetan.